REFLECTIONS OF DESTINATION QUALITY ON DESTINATION IMAGE: A CASE OF KUŞADASI - Özdemir, Gökçe (Turizam, 2020)
The image of a tourism destination is assembled on various resources including past encounters and as well as on marketing communications. However, the utmost important factor in increasing tourist arrivals is creating a sustainable tourism and a high quality of service at a destination in general. The main purpose of this study is to ascertain what image the stakeholders have in their mind about Kuşadası through ineterviews and what image the the tourists have as exemplified in the 15,047 reviews about the destination in TripAdvisor through a content analysis. The importance of this study is that it sheds light on the role and impact of destination quality on tourists’ destination image.